La critique de la littérature pour la jeunesse dans la revue InterCDI - Elisabeth Roux (Strenae)
The journal InterCDI targets IT teachers in the French education system and offers analyses of pedagogical situations and examples of educational initiatives. Its articles related to professional practice are written by teacher-researchers, though space is given to academics, researchers, and members of C.E.D.I.S as well. The magazine also reports on current debates in the profession, and on difficulties—which sometimes appear as opposition to the evolution of practices—with a constant concern for rigor and critical thinking. It also includes children's literature reviews, with the explicit aim of advising and supporting staff. By questioning the critics’ professional context based on the analysis of a six-year corpus of monthly publications (2010-2015), this article aims to define the extent to which critics present characteristics linked to the profession of its audience, under the aegis of the Ministry of National Education.